Use of Ascetic Fluid Cholesterol as a Marker to Differentiate between Types of Ascetic Fluid - Ali, Sadiq Jabar; AlKhersan, Hasan Ali; Mahdi, Hamed S. (AL-Kindy College Medical Journal, 2008)
Background:- Cholesterol is high in ascetic fluid due to malignancy and other causes of exudates. Objective:-To use cholesterol as a marker to differentiate between exudative and transudative ascetic fluid and to compare that with other routine parameters. Methods:-Twenty eight patients were included in this study 17 females with mean age of 41.9 years, 11 males with mean age of 48.2 years. The patients were divided in group I suspected transudate, and group II suspected exudate according to history and clinical examination. Ascetic fluid samples were sent for total protein, albumin, and cholesterol measurement blood samples were sent for serum protein and albumin measurement. Results:-In this study ascetic fluid cholesterol was fit with history and clinical examination to differentiate between exudative and transudative ascetic fluid. Cholesterol was a good marker when compared with ascetic fluid total protein and ascetic serum protein ratio in group I, but not in the others. Conclusion: - cholesterol can be used as a marker for the diagnosis of a cites cases but a large number of patients is important for accurate results